Self Esteem and The Tendency of Cyberbullying - Jacob, Petrus Salom Foeh; Anakaka, Dian Lestari; Wijaya, R. Pasifikus Ch (Journal of Health and Behavioral Science, 2023)
Everyone is born in weak (inferior) and tries to achieve personal or group superiority which can be in the form of positive or negative behavior. This study aims to determine the relationship between self-esteem and the tendency of cyberbullying behavior. This type of research is quantitative research with a correlational approach. Research participants are students in Kupang City. How to take samples using cluster sampling. Data collection used the Rossenberg Self Esteem Scale (Cronbach'=0.848) and the cyberbullying scale (Cronbach'=0.816) which were compiled based on cyberbullying aspects by Topcu Baker and Willard. Data analysis using Rank Spearman. The results of the analysis show that there is a significant relationship between self-esteem and the tendency of cyberbullying behavior in a negative direction.